Measurement of a multidimentional index of globalization and its impact on income inequality - Almas Heshmati (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
In this paper we present two composite indices of globalization. The first is based on the Kearney/Foreign Policy magazine and the second is obtained from principal component analysis. They indicate which countries have become most globalized and show how globalization has developed over time. The indices are composed of four components: economic integration, personal contact, technology and political engagement, each generated from a number of variables. A breakdown of the index into major components provides possibilities to identify sources of globalization and associate it with economic policy measures. The empirical results show that a low rank in the globalization process is due to political and personal factors with limited possibility for the developing countries to affect. The high ranked developed countries share similar patterns in distribution of various components. The indices were also used in a regression analysis to study the causal relationship between income inequality and globalization. Globalization indices explain only 7 to 11 per cent of the variations in income inequality among countries.
Keywords: C23; D63; F15; O57; 330; globalization; income inequality; indices; principal component; Globalisierung; Einkommensverteilung; Index; Theorie